Analyse der langfristigen Auswirkungen von Elektromobilität auf das deutsche Energiesystem im europäischen Energieverbund - Heinrichs, Heidi Ursula (Produktion und Energie / Karlsruher Institut für Technologie, Institut für Industriebetriebslehre und industrielle Produktion u. Deutsch-Französisches Institut für Umweltforschung, 2013)
This work analyses the long-term impact of electric mobility on the energy system, and aims to support the decision making of actors in the European electricity system, which takes electric mobility into account. For this purpose the Europe-wide development of electric mobility and of the energy system are examined in an integrated way based on a model coupling. This allows to analyse the interdependencies of both developments in this model-based approach endogenously.